EDUKASI PEMILIHAN BIBIT UNGGUL DAN MANAJEMEN KANDANG AYAM BROILER BAGI PETERNAK PEMULA - Rizki, Selvi Diliyanti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program aims to improve the competency of beginner broiler farmers in selecting superior breeds and implementing proper cage management techniques. Through participatory training methods, the program provides practical knowledge about breed selection criteria, cage design principles, and effective maintenance practices. The activity combines classroom sessions with hands-on practice in the field, covering topics such as recognizing quality DOC (Day Old Chicken), optimal cage density, ventilation systems, and biosecurity measures. Pre- and post-test evaluations show a 65% increase in participants' understanding, with particular improvement in breed selection skills (from 42% to 78% competency) and cage management knowledge (from 35% to 82% competency). The program results in the establishment of 5 demonstration units showing proper cage setups. This initiative significantly contributes to improving livestock productivity and economic outcomes for small-scale broiler farmers in the target area.